1998
DOI: 10.1007/s002679900105
|View full text |Cite
|
Sign up to set email alerts
|

Do Highways Influence Density of Land Birds?

Abstract: / Land bird densities in roadside habitats were studied in 17 locations in central Finland by the line transect method. Two transects were censused in each location. The first transect was situated 25 m from highway edge and the second transect 200 m away from the first one. The results suggested that land bird density was lower closer to highways. Species that avoided the road included willow warbler (Phylloscopus trochilus), crossbills (Loxia spp.), and tree pipit (Anthus trivialis). The composition of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 17 publications
3
23
1
1
Order By: Relevance
“…Our investigation is in agreement with a range of studies demonstrating the decline in numbers and species in the vicinity of roads carrying heavy traffic (Reijnen and Foppen 1994;Reijnen et al 1995;Kuitunen et al 1998, Rheindt 2003Ingelfinger and Anderson 2004;Palomino and Carrascal 2007;Benitez-López et al 2010;Summers et al 2011). An important insight emerging from our study is that the species particularly sensitive to road traffic were those nesting near the ground and with low-frequency calls.…”
Section: Discussionsupporting
confidence: 92%
“…Our investigation is in agreement with a range of studies demonstrating the decline in numbers and species in the vicinity of roads carrying heavy traffic (Reijnen and Foppen 1994;Reijnen et al 1995;Kuitunen et al 1998, Rheindt 2003Ingelfinger and Anderson 2004;Palomino and Carrascal 2007;Benitez-López et al 2010;Summers et al 2011). An important insight emerging from our study is that the species particularly sensitive to road traffic were those nesting near the ground and with low-frequency calls.…”
Section: Discussionsupporting
confidence: 92%
“…They did not examine the effect of road density, however. Other studies have found road density (van der Zande et al 1980;Hennings and Edge 2003) or distance to road (Kuitunen et al 1998;Brotons and Herrando 2001;Palomino and Carrascal 2007) to be important to bird communities, but our study is one of the few that has looked at both density and distance of different kinds of roads. Interestingly, type of road did not seem to be an important factor in determining bird communities; metrics for all roads combined were consistently selected over metrics for primary roads alone.…”
Section: Discussionmentioning
confidence: 90%
“…Higher temperatures, intensive lighting, chemical pollution and less vegetation coverage are properties common to all city environments (Slabbekoorn and Ripmeester, 2008), and these conditions are similar among all urban areas, leading to a homogeneous biodiversity (Clergeau et al, 2006;McKinney, 2006). In the case of birds, several studies have shown decreasing population densities in habitats close to anthropogenic infrastructures (van der Zande et al, 1980;Reijnen et al, 1995Reijnen et al, , 1996Kuitunen et al, 1998;Rheindt, 2003;Peris and Pescador, 2004). Along the gradient, species composition varies (Clergeau et al, 1998;Blair, 2001), the proportion between native and exotic species may change (van Heezik et al, 2008), and the same species may evolve into different subpopulations in different habitats (Badyaev et al, 2008).…”
Section: Introductionmentioning
confidence: 97%